EFFECT OF USING DIFFERENT LEVELS PERCENTAGES OF SMUT WHEAT AND SAND TREATED ON PHYSIOLOGICAL PARAMETER OF BROILER: Maha A. Al-Hemairi , Layla M. Al-Kinani , Duraid A. Abbas - Al-Hemairi, Maha A. (The Iraqi Journal of Veterinary Medicine, 2008)
This study was carried out to at the poultry farm of the college ofveterinary medicine / Baghdad University during 12/5/2004 – 6/7/2004 tostudy the effect of substitution of smut wheat instead of intact wheat inpoultry ration at the following levels (0%, 25% , 50% and 100%)representing the following groups (T0, T1, T2 and T3), respectively. Physicaltreatment was obtained for smut wheat by polishing the seed by sand toremove the superficial fungal growth. Each group was sub divided into twosub groups, one was physically treated with sand and the other was nottreated to study the hematology traits at 28 and 56 days of the experiment.Characterristics included in this study were PCV, Hb, RBC, WBC,differential leukocyte count and some of serum blood enzymes activity(ALT, AST and AP). The results obtained revealed the following:Replacing partial of smut wheat at the level of 50% or total 100%caused an imbalance of blood parameters by decreasing PCV, Hb, RBC,WBC and increased blood enzymes activity of ALT, AST and decreased APactivity. Results of differential leukocyte count revealed that heterophilswere increased while lymphocytes were decreased significantly (P<0.05) at28 and 56 days of age. Physical treatment of smut wheat by sand improve theblood parameters by rebalancing these parameter in comparison with these ofuntreated group .